Assessing cultural ecosystem services in sponge city infrastructure: a systematic review and framework proposal - Han, Nuan; Ibrahim, Roziya Binti; Mat Noor, Mohd Sallehuddin Bin (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Urbanization has significantly transformed ecological landscapes and created challenges in sustaining both environmental functionality and cultural values. In response, China’s Sponge City Infrastructure (SPI) aims to enhance urban water resilience by integrating green and blue infrastructure. While the ecological benefits of SPI have been widely studied, the cultural ecosystem services (CES) it provides remain underexplored. This study systematically reviews 61 empirical articles to evaluate how CES has been addressed in SPI-related research. Bibliometric analysis was conducted to identify CES research trends and to systematically categorize CES types, assessment methods, and evaluation indicators in SPI-related studies. The findings reveal a dominant use of non-monetary assessment methods, led by questionnaire surveys (47.5%), while monetary approaches were rarely applied. However, several limitations were identified, including the geographic concentration of studies in a few major cities, the scarcity of research on abstract CES categories (e.g., inspiration and sense of place), and the lack of measurable indicators in nearly half of the reviewed studies. To address these issues, this study proposes a context-specific CES assessment framework aligned with China’s socio-cultural conditions and planning priorities in sponge city development. The framework, based on the reviewed literature, provides a preliminary tool for evaluating CES in sponge city contexts. This work contributes to the integration of cultural ecosystem services into urban ecological planning and offers insights for sustainable development in rapidly urbanizing regions.